The Effect of Rose Bengal Purity on the Liver Function Test - Raban, P.; Gregora, V.; Brousil, J.; Jirounek, P. (Nuklearmedizin - NuclearMedicine, 1968)
Chromatographic separation of several commercial Rose Bengal preparations revealed their very variable purity. The RF and absorption maxima values indicate that the Rose Bengal preparations differ both in content and in character of coloured impurities. Most of them are radioactive so that their influencing the liver chromoexcretion test is highly probable. The validity of the presumption that they are less iodinated tetrachlorofluorescein derivatives was investigated by comparison with compounds prepared by iodination of pure tetrachlorofluorescein. However, it was demonstrated that these compounds did not appear in the Rose Bengal preparations studied and that the coloured radiochemical impurities were probably fluorescein derivatives differing by the substitution in the phthalanhydride moiety.